Identifying skills required of new epidemiologists: a content analysis of Canadian job postings and master’s programs - Chalmers, Karli E.; Spence, Kelsey L. (Frontiers in Public Health, 2024)
Introduction: The rise of emerging public health threats has increased the need for qualified epidemiologists in Canada. Our study aimed to identify the knowledge, skills, and abilities (KSAs) required of epidemiologists entering the workforce and determine whether these align with those taught in graduate epidemiology programs. Methods: An inductive content analysis of Canadian job postings from May to December 2023 containing the keyword “epidemiology” and requiring master’s degrees in epidemiology or related fields was conducted to identify the KSAs required in the workforce. Inductive content analysis of Master of Science (MSc) program descriptions and core course descriptions was completed to discern skills gained through Canadian graduate epidemiology and public health programs. Results: Based on the 295 job postings analyzed, five KSA categories were identified: communication skills (n=268, 90.8%), analytical skills (n=267, 90.5%), soft skills (n=254, 86.1%), research methodology (n=217, 73.6%), and knowledge of epidemiological concepts (n=170, 57.6%). Analysis of 18 MSc programs found that that all of them described analytical skills, research methodology, and epidemiological concepts within their curriculum. Communication skills were described in 94.4% (n=17) of programs, while soft skills were mentioned in 50.0% (n=9). However, only 66.7% (n=12) of programs outlined learning objectives or specified the skills acquired from their programs in their descriptions. Conclusions: There was alignment between the needs of the Canadian epidemiology job market and MSc programs, particularly in analytical skills and research methodology. However, development of soft skills should be emphasized within graduate epidemiology programs to better prepare graduates for the job market. Future research should aim to develop competency statements for epidemiologists in training to ensure consistency across graduate programs and promote career readiness.